Cancer Moonshot Connecting International Liquid Biopsy Efforts Through Academic Partnership. Issue 5 (22nd March 2017) - Dive, C; Shishido, SN; Kuhn, P
Abstract : The Kuhn Laboratory at the University of Southern California and the Dive Laboratory at the Cancer Research UK's Manchester Institute are teaming up to apply new cancer cell detection technology to identify patients who will progress after initial treatment. Researchers will take a simple blood sample to identify early those patients whose cancer has returned, while analyzing circulating tumor cells (CTCs) in great detail, providing new clues on the most effective therapy for the patient's cancer.